2021
DOI: 10.1108/jarhe-02-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of barriers to Iranian ESP instructors’ reflective practice scale

Abstract: PurposeSince reflectivity has a crucial role in education, it has attracted researchers’ attention in the last decades. As such, the present study aimed to construct and validate a questionnaire to assess the barriers to reflective practices of Iranian ESP (English for Specific Purposes) instructors. Furthermore, this study aimed to investigate the reliability of the scale.Design/methodology/approachTo attain the purpose of the study, the researchers developed the first item pool of the questionnaire which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The second factor included the items related to teachers' issues. The findings are compatible with Soodmand Afshar and Farahani (2018), and Sheikhbanooie and Farahian (2021), who concluded that teachers' unfamiliarity with reflective practice, their lack of motivation, and absence of adequate training on reflection are among the major inhibitors of teachers' reflective practices. The results of the present study have also extended prior research by Jaeger's (2013) since he found that some of the major inhibitors to reflective practice are teachers' certain personal characteristics, their lack of skills and experience, school and district structures that negatively affects reflective behaviour, and teachers' limitations of the profession (Jaeger, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The second factor included the items related to teachers' issues. The findings are compatible with Soodmand Afshar and Farahani (2018), and Sheikhbanooie and Farahian (2021), who concluded that teachers' unfamiliarity with reflective practice, their lack of motivation, and absence of adequate training on reflection are among the major inhibitors of teachers' reflective practices. The results of the present study have also extended prior research by Jaeger's (2013) since he found that some of the major inhibitors to reflective practice are teachers' certain personal characteristics, their lack of skills and experience, school and district structures that negatively affects reflective behaviour, and teachers' limitations of the profession (Jaeger, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Scant attention has been paid to the barriers of reflective thinking and those studied which have been carried out have dealt with reflective practice, that is teachers' reflectivity (e.g., Kavanoz & Akbaş, 2017;Moradkhani & Shirazizadeh, 2017;Sheikhbanooie & Farahian, 2021;Soodmand Afshar & Farahani, 2018;Tajik & Ranjbar, 2018).…”
Section: Critical Reflectionmentioning
confidence: 99%
See 1 more Smart Citation